COMPARATIVE ANALYSIS OF DAILY DAWN AND THE HINDU: EXAMINING CPEC NARRATIVES - Waleed Ahmad; Zarmina Gul (International Journal of Contemporary Issues in Social Sciences, 2024)
This study, titled "Comparative Analysis of Daily Dawn and The Hindu Coverage Examining CPEC Narratives," examines how print media in Pakistan and India portray the China-Pakistan Economic Corridor (CPEC), with a focus on Daily Dawn and The Hindu. Grounded in framing theory, the study investigates how these newspapers selectively emphasize specific features of CPEC to influence public perception. The study uses content analysis to explore the dominant frames applied to key aspects such as infrastructure development, international stakeholder responses, and the portrayal of CPEC as either an economic or political endeavor. The findings show that Daily Dawn adopts a predominantly optimistic tone, with an emphasis on infrastructure and development (22.73%), the security of Chinese workers (20.45%), and international collaboration (20.45%). In contrast, The Hindu emphasizes infrastructure (33.33%) but frames CPEC through a political lens, with 22.22% of its coverage portraying the project as a geopolitical threat to Indian sovereignty. These opposing perspectives illustrate the media's role in shaping national narratives, while also highlighting the broader implications for regional relations and the development of public opinion regarding CPEC.